Molecular insight in the multifunctional activities of Withaferin A - Vanden Berghe, Wim; Sabbe, Linde; Kaileh, Mary; Haegeman, Guy; Heyninck, Karen (Biochemical pharmacology, 2012)
Herbal medicine which involves the use of plants for their medicinal value, dates as far back as the origin of mankind and demonstrates an array of applications including cardiovascular protection and anti-cancer activities, via antioxidant, anti-inflammatory and metabolic activities. Even today the popularity of medicinal herbs is still growing like in traditional medicines such as the Indian medicine, Ayurveda. One of the Ayurvedic medicinal plants is Withania somnifera Dunal, of which the important constituents are the withanolides. Among them, Withaferin A is one of the most bioactive compounds, exerting anti-inflammatory, pro-apoptotic but also anti-invasive and anti-angiogenic effects. In the context of modern pharmacology, a better insight in the underlying mechanism of the broad range of bioactivities exerted by Withaferin A is compulsory. Therefore, a lot of effort was made to explore the intracellular effects of Withaferin A and to characterize its target proteins. This review provides a decisive insight on the molecular basis of the health-promoting potential of Withaferin A.